Developing Listening Skills for Speech Texts Using Articulate Storyline in Grade VIII of Junior High School - Febi Putri Utami; Subyantoro; Tommi Yuniawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study focuses on the need for effective learning media in teaching listening skills in speech texts at the junior high school level. This article aims to develop and evaluate the effectiveness of learning media based on the Articulate Storyline in improving students' ability to listen to speech texts. The research method used is research and development with a one-group pretest-posttest design. Data were collected through pretests and posttests, followed by normality tests and paired sample t-tests to evaluate the significance of the results. The results showed that the Articulate Storyline media that had been improved based on expert input proved effective, with a significant increase in student learning outcomes from pretest to posttest. The normality test confirmed the normal distribution of the data, and the paired sample T-test showed a substantial difference between the pretest and posttest, supporting the hypothesis that this medium positively impacts students' ability to listen to speech texts. This study concludes that the Articulate Storyline media is an effective and useful learning tool for improving the listening skills of speech texts in junior high school students.